Microfragmented Adipose Tissue Versus Platelet-Rich Plasma for the Treatment of Knee Osteoarthritis: A Prospective Randomized Controlled Trial at 2-Year Follow-up. Issue 11 (September 2022) - Zaffagnini, Stefano; Andriolo, Luca; Boffa, Angelo; Poggi, Alberto; Cenacchi, Annarita; Busacca, Maurizio; Kon, Elizaveta; Filardo, Giuseppe; Di Martino, Alessandro
Background: Intra-articular microfragmented adipose tissue (MF-AT) injections have been proposed for the treatment of knee osteoarthritis (OA). Purpose: To compare a single injection of MF-AT or platelet-rich plasma (PRP) in terms of clinical outcomes and OA progression. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 118 patients with symptomatic knee OA were randomized to receive a single intra-articular injection of MF-AT or PRP. Patients were evaluated before the injection and at 1, 3, 6, 12, and 24 months with the International Knee Documentation Committee (IKDC) subjective score, Knee injury and Osteoarthritis Outcome Score (KOOS) subscales, EuroQol visual analogue scale (EQ-VAS), EuroQol 5 dimensions (EQ-5D), and visual analogue scale (VAS) for pain. Primary outcomes were the IKDC subjective score and the KOOS pain subscore at 6 months. Knees were evaluated at baseline and at 6, 12, and 24 months with radiography and high-resolution magnetic resonance imaging (MRI) using the Whole-Organ Magnetic Resonance Imaging Score (WORMS). Results: Both MF-AT and PRP provided a statistically and clinically significant improvement up to 24 months. The improvement in the IKDC subjective score from baseline to 6 months was similar in both MF-AT (41.1 ± 16.3 to 57.3 ± 18.8) and PRP (44.8 ± 17.3 to 58.4 ± 18.1) groups ( P < .0005). The improvement in the KOOS pain subscore from baseline to 6 months was similar in both the MF-AT (58.4 ± 15.9 to 75.8 ± 17.4) and PRP (63.5 ± 17.8 to 75.5 ± 16.1) groups ( P < .0005). Overall, no differences were found between the MF-AT and PRP groups in terms of clinical outcomes, adverse events (18.9% and 10.9%, respectively), and failures (15.1% and 25.5%, respectively). Radiographic and MRI findings did not show changes after the injection. As a secondary outcome, more patients in the MF-AT group with moderate/severe OA reached the minimal clinically important difference for the IKDC score at 6 months compared with the PRP group (75.0% vs 34.6%, respectively; P = .005). Conclusion: A single intra-articular injection of MF-AT was not superior to PRP, with comparable low numbers of failures and adverse events and without disease progression. No differences were found in clinical and imaging results between the 2 biological approaches.